Evaluasi Laju Pemberian Pakan dan Rasio Konversi Pakan sebagai Indikator Efisiensi Domestikasi Ikan Betutu (Oxyeleotris marmorata) pada Sistem Kolam Terpal - Syaiful Ramadhan Harahap; Toni Anggara; Andi Yusapri; Khairul Ihwan; Arief Rachman B; Abdul Gani; Muhammad Thaha; Gusmanto Gusmanto (Program Studi Pendidikan Biologi, Universitas Riau Kepulauan, 2026)
Marble goby (Oxyeleotris marmorata) production relies heavily on wild catches, creating a need for feed-efficient domestication strategies to support sustainable aquaculture. This study evaluated the feeding rate (FR), feed conversion ratio (FCR), specific growth rate (SGR), and survival of marble goby reared in tarpaulin ponds. Fifteen fish were cultured for 56 days in three ponds, with five fish per pond, and fed twice daily with chopped fresh trash fish to apparent satiation. The data were assessed descriptively and using quadratic polynomial regression. The mean FR ranged from 1.30 to 1.75% biomass day⁻¹, cumulative FCR from 6.53 to 10.67, and cumulative SGR from 0.19 to 0.26% day⁻¹. Pond 1 showed the most balanced performance, with an FCR of 6.53, biomass gain of 154 g, and 100% survival, whereas Pond 2 experienced 40% mortality. The FR–SGR relationship followed a quadratic pattern, with a stationary point at 1.45% biomass day⁻¹ (R² = 0.3804). This value represents an efficient feeding range rather than a definitive optimum. Controlled feeding in tarpaulin ponds supports early-stage domestication and may reduce dependence on wild marble goby stocks.